1998
DOI: 10.1007/s004270050152
|View full text |Cite
|
Sign up to set email alerts
|

Cytological evidence of spontaneous androgenesis in the freshwater clam Corbicula leana Prime

Abstract: Cytological observations and DNA microfluorometry of the hermaphrodite freshwater triploid clam Corbicula leana revealed unusual androgenetic development as follows: (1) the maternal genome of zygotes was extruded as two polar bodies just after karyokinesis of the first meiosis, (2) only chromosomes derived from one male pronucleus constituted the metaphase of the first cleavage of zygotes, (3) DNA content of 7-day-old veliger larvae was identical to the somatic cells of the parent. This spontaneous androgenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 8 publications
(9 reference statements)
1
55
0
3
Order By: Relevance
“…Within the current (and largely unresolved) taxonomy, at least four morphologically distinct, hermaphroditic species reproduce via androgenesis. For two of the four species (C. leana and C. fluminea), androgenesis was identified through cytological examination of fertilization events [3][4][5]. For two additional species (C. australis and C. fluminalis), androgenesis is inferred from the observation of extremely low genetic diversity, polyploidy and biflagellate sperm (a presumed biomarker of androgenesis [46]).…”
Section: (B) Clams Of the Genus Corbiculamentioning
confidence: 99%
See 1 more Smart Citation
“…Within the current (and largely unresolved) taxonomy, at least four morphologically distinct, hermaphroditic species reproduce via androgenesis. For two of the four species (C. leana and C. fluminea), androgenesis was identified through cytological examination of fertilization events [3][4][5]. For two additional species (C. australis and C. fluminalis), androgenesis is inferred from the observation of extremely low genetic diversity, polyploidy and biflagellate sperm (a presumed biomarker of androgenesis [46]).…”
Section: (B) Clams Of the Genus Corbiculamentioning
confidence: 99%
“…As we explain in the following sections, whether and how diploidization occurs, and under which form of sex determination, greatly affects the predicted fate of androgenetic lineages. While androgenesis is rare in nature, it is 'normal' in some natural populations, including clams of the genus Corbicula [3][4][5], a conifer [6][7][8], a few ants [9][10][11][12] and stick insects [13][14][15][16], and most likely an Australian carp gudgeon [17] (table 1). Androgenesis is also seen sporadically in some species, particularly hymenopterans (ants, bees and wasps), and in some monocots, dicots and gymnosperms (table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In C. leana and C. fluminea, the oocyte never goes through meiosis II, as the entire maternal nuclear genome is extruded during the first round of meiosis, and thus the reproductive mode is androgenetic Ishibashi et al, 2003). Komaru et al (1998) hypothesized that this unusual phenomenon of axis orientation and complete expulsion of maternal chromosomes in androgenetic Corbicula would result from a 'meiosis-specific mutation' , leading to the alteration of the orientation of the axis of the meiotic spindle. Furthermore, Komaru et al (2000) suggested that androgenesis could also be caused by an alteration in the attachment site of the centrosomes.…”
Section: Fertilization and Maternal Meiosis In Androgeneticmentioning
confidence: 99%
“…(Form A) described by Lee et al (2009) in the USA and C. leana described by Park and Kim (2003) in Asia. It should be noted that androgenesis is a common feature of the Corbicula genus (Komaru and Kawagishi, 1998;Byrne et al, 2000;Ishibashi et al, 2003), which compromises analysis relying only on mitochondrial sequences as conducted in this study i.e., distinct nuclear lineages can be grouped in the same mitochondrial cluster (Park and Kim, 2003;Hedtke et al, 2008;Pigneur et al, 2011). Further genetic studies, combining nuclear and mitochondrial data along with detailed morphological examination, should thus be carried out for a definite genetic comparison of the two populations of interest.…”
Section: Discussionmentioning
confidence: 91%